Trust agents : using the web to build influence, improve reputation, and earn trust - Brogan, Chris, ....-; Smith, Julien, ....- (Hoboken : John Wiley & Sons, 2010)
Today's online influencers are Web natives who trade in trust, reputation, and relationships, using social media to accrue the influence that builds up or brings down businesses online. In Trust Agents, two social media veterans show you how to tap into the power of social networks to build your brand's influence, reputation, and, of course, profits. In this revised paperback version, learn how businesses are using the latest online social tools to build networks of influence and how you can use those networks to positively impact your business. Combining high-level theory and practical actions, this guide delivers actionable steps and case studies that show how social media can positively impact your business. New edition features specific first moves for entering social media for small businesses, educators, travel and hospitality enterprises, nonprofit organizations, and corporations Authors both have a major presence on the social Web as well as years of online marketing and new media experience If you want your business to succeed, don't sit on the sidelines while new markets and channels grow. Instead, use the Web to build trust with your consumers using Trust Agents.
Keywords: Marketing -- Internet